The Translator as a Mediator of Pragmatic Meaning in English–Uzbek Literary Translation - Ro'ziyeva Nilufar Jaxongirovna; Soliyeva M.A (MULTIDISCIPLINARY JOURNAL: FUNDAMENTAL RESEARCH SCIENTIFIC JOURNAL, 2025)
Abstract: This article investigates the role of the translator as a mediator of pragmatic meaning in English–Uzbek literary translation. Literary texts often contain culturally embedded expressions, speech acts, idioms, and context-dependent nuances that carry significant pragmatic value. Translators are tasked not only with transferring the literal meaning but also with conveying the intended communicative effect, preserving politeness, tone, and cultural subtleties. Through analysis of selected English literary excerpts and their Uzbek translations, this study identifies common challenges in maintaining pragmatic meaning and examines strategies used by translators, such as explicitation, adaptation, and compensation. The research underscores the importance of pragmatic awareness, cultural competence, and interpretive skill in producing accurate and culturally sensitive literary translations.